Peningkatan Promosi Usaha Catering UMKM Melalui Pembuatan Website Berbasis WordPress - Tianti, Astrida Misna; Firmania, Baitul Nazwa; Prini; Fanani, Reza Cahya Putra; Putri, Sapna Estevania; Adisusilo, Anang Kukuh; Prini, Prini (PENITI BANGSA (Pemanfaatan Ilmu Pengetahuan dan Teknologi bagi Masyarakat), 2024)
Micro, Small and Medium Enterprises (MSMEs) have an important role in the regional economy by creating jobs and encouraging innovation. However, they often experience difficulties in promoting their products and services to the public, thereby hampering the potential for business growth. One example is a catering business owner, namely Rangga, who faces challenges in expanding his market reach and increasing his business potential because they still rely on manual promotions such as word of mouth marketing. In overcoming these challenges, creating a promotional website using the WordPress platform is the right solution. With this website, MSMEs like Rangga can increase their online presence, increase the number of customers and business profits. Not only that, this online presence also makes it easier for customers to place orders online, thereby speeding up the transaction process. This catering business promotion website has been successfully created and implemented. Through the web address provided, users can access complete information regarding menus, prices, and customer testimonials from catering services.